Characteristic of EBT-XD and EBT3 radiochromic film dosimetry for photon and proton beams. (15th March 2018) - Khachonkham, Suphalak; Dreindl, Ralf; Heilemann, Gerd; Lechner, Wolfgang; Fuchs, Hermann; Palmans, Hugo; Georg, Dietmar; Kuess, Peter
Abstract: Recently, a new type of radiochromic film, the EBT-XD film, has been introduced for high dose radiotherapy. The EBT-XD film contains the same structure as the EBT3 film but has a slightly different composition and a thinner active layer. This study benchmarks the EBT-XD against EBT3 film for 6 MV and 10 MV photon beams, as well as for 97.4 MeV and 148.2 MeV proton beams and 15–100 kV x-rays. Dosimetric and film reading characteristics, such as post irradiation darkening, film orientation effect, lateral response artifact (LRA), film sensitivity, energy and beam quality dependency were investigated. Furthermore, quenching effects in the Bragg peak were investigated for a single proton beam energy for both film types, in addition measurements were performed in a spread-out Bragg peak. EBT-XD films showed the same characteristic on film darkening as EBT3. The effects between portrait and landscape orientation were reduced by 3.1% (in pixel value) for EBT-XD compared to EBT3 at a dose of 2000 cGy. The LRA is reduced for EBT-XD films for all investigated dose ranges. The sensitivity of EBT-XD films is superior to EBT3 for doses higher than 500 cGy. In addition, EBT-XD showed a similar dosimetric response for photon and proton irradiation with low energy and beam quality dependency. A quenching effect of 10% was found for both film types. The slight decrease in the thickness of the active layer and different composition configuration of EBT-XD resulted in a reduced film orientation effect and LRA, as well as a sensitivity increase in high-dose regions for both photon and proton beams. Overall, the EBT-XD film improved regarding film reading characteristics and showed advantages in the high-dose region for photon and proton beams.